2014
DOI: 10.1007/s13277-014-2357-3
|View full text |Cite
|
Sign up to set email alerts
|

GOLPH3 high expression predicts poor prognosis in patients with resected non-small cell lung cancer: an immunohistochemical analysis

Abstract: Golgi phosphoprotein 3 (GOLPH3) has been reported to be involved in the development of several human tumours. However, little is known about GOLPH3 expression and its clinical significance in non-small cell lung cancer (NSCLC). The present study was conducted to investigate the expression of GOLPH3 and its prognostic significance in NSCLC. Immunohistochemical analysis was used to determine the expression of GOLPH3 in 145 cases NSCLC tissue and their corresponding adjacent normal tissues. The results are the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 27 publications
(28 reference statements)
3
18
0
Order By: Relevance
“…We found that the expression level of GOLPH3 is closely related to the M classification in tissue sections, which is consistent with other studies [8,12]. We also found that GOLPH3 can regulate the migration and invasion abilities of NSCLC cell lines, including A549 and L78; meanwhile, the invasion and migration of these cell lines was reduced when GOLPH3 was knocked down using siRNA.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We found that the expression level of GOLPH3 is closely related to the M classification in tissue sections, which is consistent with other studies [8,12]. We also found that GOLPH3 can regulate the migration and invasion abilities of NSCLC cell lines, including A549 and L78; meanwhile, the invasion and migration of these cell lines was reduced when GOLPH3 was knocked down using siRNA.…”
Section: Discussionsupporting
confidence: 91%
“…As determined by IHC staining, 144 of 230 NSCLC tissue sections displayed moderate to strong staining of GOLPH3, whereas there was no significant GOLPH3 staining in the adjacent, non-cancerous tissue. Statistical analysis revealed that the expression level of GOLPH3 was correlated with the M classification and clinical stage, supporting the notion that GOLPH3 might play an important role in the progression of NSCLC, which was consistent with Zhang's study [12], whereas it was not in agreement with Lu's study reporting that GOLPH3 expression did not correlate with the clinicopathological features of early-stage NSCLC [13]. This inconsistency may be due to differences in the clinical stages of NSCLC; while there was no relationship between GOLPH3 expression and early-stage.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Evidence of transformation by overexpression of GOLPH3 has been reported in MDA-MB-231 and MCF7 breast cancer cell lines (911), and U251 and U87 glioblastoma cell lines (12, 13). Frequent overexpression of GOLPH3 and correlation with poor prognosis have been reported in multiple tumor types including 58–72% of non-small cell lung cancers (14, 15), 52% of breast cancers (11), 70% of prostate cancers (16), 73% of pancreatic ductal adenocarcinomas (17), 65% of hepatocellular carcinomas (18, 19), 55–58% of gastric cancers (20, 21), 53% of renal cell carcinomas (22), 41–53% of glioblastomas (12, 23, 24), 49% of esophageal squamous carcinomas (25), and 45% of ovarian carcinomas (26, 27). Overexpression of GOLPH3 occurs frequently in rhabdomyosarcoma, and knockdown of GOLPH3 in rhabdomyosarcoma cell lines impairs cell proliferation (28).…”
Section: Golph3 Is An Oncogenementioning
confidence: 99%